GLP-1 Receptor Agonists’ Impact on Fertility - A Review - Joanna Wojda; Katarzyna Lesiczka-Fedoryj; Anna Walczak; Zuzanna Kościuszko; Adam Sobiński; Matylda Czerwonka; Katarzyna Kurza; Julianna Podolec; Silvia Ciraolo; Agnieszka Kulczycka-Rowicka (Quality in Sport)
Purpose of Research: The aim of the research is to summarize the impact of GLP-1 analogs on fertility according to clinical studies, particularly in obese or overweight women with PCOS.